Disaster Preparedness of Generation Y Nurses and Related Factors. - SİMSEK, Yunus; ALAN, Handan (Fenerbahce University Journal of Health Sciences (FBU-JOSH) / Fenerbahçe Üniversitesi Sağlık Bilimleri Dergisi, 2025)
Generation Y nurses constitute the majority of hospital staff. Therefore, it is important to determine the influencing factors by understanding their core competencies in the event of a disaster. The purpose of this study is to determine the core competencies of Generation Y nurses in disaster situations and to compare their personal and professional characteristics and experiences in disaster situations. The study was designed as a descriptive cross-sectional study with an online survey that included demographic information and the Nurses’ Perceptions of Disaster Core Competencies Scale and conducted with 408 participants. The mean score of Generation Y nurses on the NPDCC was 151.18±30.11, and according to the subscales, they scored the highest on infectious diseases and outbreaks (6.04±3.04) and the lowest on nuclear accident preparedness (3.21±2.26). Educational level and the institution in which they work were found to be statistically significant differences in overall NPDCC in comparisons by nurses’ personal and professional characteristics, with postgraduates and nurses working in a university hospital scoring higher (p<.01). However, the marital status, position and unit variables did not cause a statistically significant difference in the overall NPDCC score (p>.05). It is recommended that disaster core competency training programmes take into account generational differences.